Construction of a novel DNA-based comparator and its application in intelligent analysis. Issue 35 (27th August 2019) - Huang, Dan; Guo, Chen; Miao, Jiarong; Zhang, Yi; Lin, Xiao; Chen, Die; Yang, Shu; Yang, Qianfan; Tang, Yalin
Abstract : A novel and general DNA-based comparator that can directly weigh the predominant bacterium in a complex biological matrix precisely was constructed. Abstract : In this work, a novel and general comparator was constructed based on cascaded strand displacement reactions and DNA hybridization and its potential in intelligently weighing the quantitative predominance of two targets was explored in a complex biological matrix, which not only enriches the information processing mode of DNA computation but also provides an instructive way to deal with quantitative analyzing tasks in further DNA-based logic sensors.